2010
DOI: 10.1021/nn901344u
|View full text |Cite
|
Sign up to set email alerts
|

Direct Patterning of Intrinsically Electron Beam Sensitive Polymer Brushes

Abstract: The fabrication of patterned polymer brushes has attracted considerable attention as these structures can be exploited in devices on the nano- and microscale. Patterning of polymer brushes is typically a complex, multistep process. We report the direct patterning of poly(methyl methacrylate) (PMMA), poly(2-hydroxyethyl methacrylate) (PHEMA), poly(isobutyl methacrylate) (PIBMA), poly(neopentyl methacrylate) (PNPMA), and poly(2,2,2-trifluoroethyl methacrylate) (PTFEMA) brushes in a single step by electron beam (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(76 citation statements)
references
References 50 publications
(61 reference statements)
1
75
0
Order By: Relevance
“…The synthesis, processing and characterization of such complex brush structures, for example, mixed brushes [193][194][195][196][197], multiblock copolymer brushes [114,115,198], gradient polymer brushes [199,200], nanopatterned polymer brushes [107,116], polymer carpet/Janus membrane [8,[201][202][203] and polymer nanochannels [114,117] are of great interest from a fundamental as well as technological perspective. Comprehensive understanding of structure-property relationships in well-defined and fully characterized polymer brushes aided by new synthesis as well as predictive modeling can open up newer applications for polymer brushes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesis, processing and characterization of such complex brush structures, for example, mixed brushes [193][194][195][196][197], multiblock copolymer brushes [114,115,198], gradient polymer brushes [199,200], nanopatterned polymer brushes [107,116], polymer carpet/Janus membrane [8,[201][202][203] and polymer nanochannels [114,117] are of great interest from a fundamental as well as technological perspective. Comprehensive understanding of structure-property relationships in well-defined and fully characterized polymer brushes aided by new synthesis as well as predictive modeling can open up newer applications for polymer brushes.…”
Section: Discussionmentioning
confidence: 99%
“…Top-down patterning through lithography was adapted to pattern polymer brushes synthesized by bottom-up "grafting-from" approach. Rastogi et al reported the direct patterning of several methacrylate-based polymer brushes that were exposed to e-beam lithography resulting in a patterned polymer brush surface [116]. Paik et al further showed that e-beam patterning of P(S-b-MMA) brushes created by SIP led to nanochannels, as the upper layer (PS) was crosslinked (negative tone resist) and the bottom layer (PMMA) was degraded upon e-beam exposure (positive tone resist) [117] (Figure 6b).…”
Section: Micro-and Nano-patterned Brushesmentioning
confidence: 99%
“…The living nature of the ATRP was evident by the appearance of the fluorine atom which is the elemental marker for the pTFEMA brushes. [52][53][54] The high resolution F 1s signal (690 eV) increased proportionally with increasing LbL brush films as shown in Figure 4 accordance with the LbL technique, as the number of macroinitiator layers deposited on the surface increased so did the initiator density. [38e] Having more layers deposited on the surface translated to increasing active sites available for initiating the polymerization.…”
Section: Xps Characterization Of the P(st) And P(st-b-tfema) Brushesmentioning
confidence: 60%
“…These values of over 1008 are consistent with the hydrophobic nature of the semifluorinated pTFEMA brushes. [43,[52][53][54] Figure 2(c) displays visual representations of the water contact angle taken from the LbL 20 macroinitiator film and its subsequent polymerizations.…”
Section: Si-atrp Of P(st) Homopolymer and P(st-b-tfema) Block Copolymmentioning
confidence: 99%
“…For the latter application, polymeric materials, and in particular self-assembling block copolymers, are employed to build up tunable nanomasks for subsequent nano-patterning processes. This approach is widely investigated since it is emerging as a simple, cost-effective, versatile, and scalable technique to generate scaffolds and templates for the fabrication of nano-structured devices [1,2]. In more details, the technology leading to lithographic nanomasks involves a multistep thermal procedure [3][4][5] in which a block copolymers thin film (30 nm) is deposited on an ultra-thin layer (2-9 nm) of a grafted functional random copolymer (RCP), which acts as surface modifier.…”
Section: Introductionmentioning
confidence: 99%